The Application of AHP and PESTEL-SWOT Analysis on The Study of Military Amphibious Aircraft Acquisition Decision Making in Indonesia - Bimo, Emanuel Ario; Prabawa, Eka; Sembiring, Esra Kriahanta; Ramsi, Oktaheroe; Sjamsoeddin, Sjafrie; Yusgiantoro, Purnomo; Midhio, I Wayan (Technium Social Sciences Journal, 2022)
Indonesia’s characteristics as an archipelagic state along with the increase of traditional and non-traditional threats in Indonesia require the ownership of military amphibious aircraft to oversee its maritime territories and perform logistics distribution to remote areas with minimum accessibility, especially its outermost islands. This study applied a combination of analytic hierarchy process (AHP), Political, Economic, Social, Techonology, Environment, and Legal (PESTEL) and Strength, Weakness, Opportunity, and Threat (SWOT) analysis to conduct a structured, systematic, measurable, and comprehensive decision-making process for selecting military amphibious aircraft and prescribe strategic recommendations on the acquisition plan. By using 3 criteria, 14 sub-criteria, and 3 alternative aircraft models, the results of AHP analysis showed that the Beriev Be-200 aircraft are the most preferred aircraft by the Indonesian users. The results of PESTEL-SWOT analysis show that good diplomatic relations between Indonesia and the manufacturer’s country of origin, users’ support to the plan, and user’s ability to adapt in operating and maintaining the aircraft support this decision. Meanwhile, limited fiscal capacity and domestic aircraft maintenance facilities/depots, as well as the risk of spare parts scarcity, have to be addressed for Indonesia to acquire its own military amphibious aircrafts.